Effect of the distribution of dividend in the return of the action in Chile - Fuenzalida, Darcy (2003)
There have been many studies in the field of dividends in the last twenty seven years. The aim of this paper is to contrast the Barclay study (1987), and to complement Venkatesh study (1989).In this research, we conclude that, in Chile, contrary to Barclay is conclusion, the share returns, immediately after the date of closing, do not show a drop in the amount of the dividend. Finally, complementing Venkatesh study, we reached the conclusion that the average volatibility of the twenty five day prior to the closing is lower than that of the twenty five days following the closing.